2023
DOI: 10.1186/s13148-023-01581-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal adverse childhood experiences (ACEs) and DNA methylation of newborns in cord blood

Phillip Collender,
Anne K. Bozack,
Stephanie Veazie
et al.

Abstract: Background Adverse childhood experiences (ACEs) increase the risk of poor health outcomes later in life. Psychosocial stressors may also have intergenerational health effects by which parental ACEs are associated with mental and physical health of children. Epigenetic programming may be one mechanism linking parental ACEs to child health. This study aimed to investigate epigenome-wide associations of maternal preconception ACEs with DNA methylation patterns of children. In the Center for the He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…We must also acknowledge limitations of our study. First, we did not measure certain factors that have been associated with methylation of specific loci in cord blood cells and, therefore, could potentially influence our results, such as maternal exposure to environmental endocrine disruptors [ 68 ] and green space [ 40 ] during pregnancy or maternal adverse childhood experiences [ 69 ]. We excluded women with clinical depression, but attention should be also paid to maternal depressed mood during pregnancy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We must also acknowledge limitations of our study. First, we did not measure certain factors that have been associated with methylation of specific loci in cord blood cells and, therefore, could potentially influence our results, such as maternal exposure to environmental endocrine disruptors [ 68 ] and green space [ 40 ] during pregnancy or maternal adverse childhood experiences [ 69 ]. We excluded women with clinical depression, but attention should be also paid to maternal depressed mood during pregnancy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one report, mothers exposed to 4 or more ACEs had a 3.74 times risk for low birth weight (0.050 vs. 0.187) and a 1.74 times greater risk for prematurity (0.085 vs. 0.148) than those whose mothers reported no ACE exposure ( 216 ). The biological basis for adverse early childhood events leading to adverse maternal and fetal outcomes later in life may be explained by epigenetic changes and DNA methylation ( 217 ). Social inclusion and non-discrimination …”
Section: Part II Effect Of Racial and Social Determinants Of Health O...mentioning
confidence: 99%
“…19,20 Multiple studies have reported that ACEs are associated with advanced epigenetic aging. [21][22][23][24][25][26] In previous studies, investigators found that maternal ACEs were associated with epigenome-wide changes in DNA methylation in newborn cord blood 27,28 and in epigenetic aging changes in children. 29 Evidence suggests that altered epigenetic aging can be programmed early in development, 30 even in utero, increasing disease risk over a person's lifespan.…”
Section: Introductionmentioning
confidence: 99%